Pork, Infrastructure and Growth: Evidence from the Italian Railway Expansion - Roberto Bonfatti; Giovanni Facchini; Alexander Tarasov; Gian Luca Tedeschi; Cecilia Testa (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies the role played by politics in shaping the Italian railway network, and its impact on long-run growth patterns. Examining a large state-planned railway expansion that took place during the second half of the 19th century in a recently unified country, we first study how both national and local political processes shaped the planned railway construction. Exploiting close elections, we show that a state-funded railway line is more likely to be planned for construction where the local representative is aligned with the government. Furthermore, the actual path followed by the railways was shaped by local pork-barreling, with towns supporting winning candidates more likely to see a railway crossing their territory. Finally, we explore the long-run effects of the network expansion on economic development. Employing population and economic censuses for the entire 20th century, we show that politics at a critical juncture played a key role in explaining the long-run evolution of local economies.
Keywords: N01; N73; D72; 330; infrastructural development; political economy